Novel hybrid multifunctional magnetoelectric porous composite films - Martins, Pedro Libânio Abreu (2015)
Novel multifunctional porous films have been developed by the integration of magnetic CoFe2O4 (CFO) nanoparticles into poly(vinylidene fluoride)-Trifuoroethylene (P(VDF-TrFE)), taking advantage of the synergies of the magnetostrictive filler and the piezoelectric polymer. The porous films show a piezoelectric response with an effective d33 coefficient of -22 pC/N-1, a maximum magnetization of 12 emu.g-1 and a maximum magnetoelectric coefficient of 9 mV.cm-1.Oe-1. In this way, a multifunctional membrane has been developed suitable for advanced applications ranging from biomedical to water treatment.